FAMILI BARU METODE ITERASI BERORDE TIGA UNTUK MENEMUKAN AKAR GANDA PERSAMAAN NONLINEAR - Nurul Khoiromi; Imran M.; Supriadi Putra (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
In this article, we discuss a new family iterative method derived from a linear combi-nation of Osada’s and Euler-Chebyshev’s for multiple roots. Analytically, it is shown that the method is of order three. Furthermore, by choosing the certain values of the parameter in the new family iterative methods, several well-known methods and new iterative methods are obtained. Numerical comparisons between the proposed iterative methods and well-known methods are carried out by looking at the number of iterations and number of function evaluations.